La forme transmoderne des pratiques récréatives de nature - Jean Corneloup (Développement Durable et Territoires)
This article puts forwards an approach to outdoor recreational practices by presenting the basics of an emerging cultural form: the transmodern form, which originates in the history of our societies and has become a contemporary and dynamic form. Faced with the current social stakes and in touch with the demands and the yearnings of the individuals, some stakeholders and audiences have started to try and reshape the uses which are made of nature, technologies and sports practices. This paper aims at presenting the outlines of this transmodern form.